The Analysis of Information Processing Methods to Assess Reliability of Machines and Equipment - Gafarzada, H.V.; Gafarov, A.M.; Khankishiyev, I.A. (Herald of Azerbaijan Engineering Academy, 2023)
In the article, the issues of analysis of the methods of processing the results of the studies conducted for the evaluation of reliability parameters of machines and equipment were considered. For this purpose, the possibility of applying the basic principles and laws of Probability Theory and Mathematical Statistics was investigated.